Associations between histologic features of nonalcoholic fatty liver disease (NAFLD) and quantitative diffusion‐weighted MRI measurements in adults. Issue 6 (25th September 2014) - Murphy, Paul; Hooker, Jonathan; Ang, Brandon; Wolfson, Tanya; Gamst, Anthony; Bydder, Mark; Middleton, Michael; Peterson, Michael; Behling, Cynthia; Loomba, Rohit; Sirlin, Claude
<x xml:space="preserve">Abstract</x> Purpose To investigate in adults the associations between histologic features of nonalcoholic fatty liver disease (NAFLD) and quantitative measures derived from diffusion‐weighted imaging (DWI). Materials and Methods Eighty‐nine adults undergoing standard‐of‐care liver biopsy for NAFLD were recruited for DWI. Biopsies were scored for histologic features of NAFLD. DWI was performed using b‐values of 0, 100, and 500 s/mm2. Images were reconstructed using either conventional magnitude averaging (CMA) or a method to address bulk motion artifacts (Beta*LogNormal, BLN). The apparent diffusion coefficient (ADC) and the diffusivity (D) and perfusion fraction (F) of the intravoxel incoherent motion (IVIM) model were measured in the right hepatic lobe using both reconstructions. Associations between histologic features and DWI‐derived measures were tested statistically with several methods including multiple linear regression. Results Using CMA and BLN reconstructions, respectively, the means (and ranges) were 1.7 (1.1–3.5) and 1.4 (1.0–3.2) × 10–3mm2/s for ADC, 1.1 (0.84–1.4) and 0.84 (0.53–1.1) × 10–3mm2/s for D, and 17 56789101112131415161718192021222324252627282930313233 and 18 (2.3–35)% for F. For both reconstruction methods, D decreased with steatosis and F decreased with fibrosis (P < 0.05). ADC was not independently associated with any histologic feature. Conclusion Steatosis and fibrosis have significant independent effects on D and F in adults undergoing biopsy for NAFLD. J. Magn. Reson. Imaging 2015;41:1629–1638. © 2014 Wiley Periodicals, Inc.